SOCIAL AND SHARIAH ACCOUNTABILITY IN DIGITAL ISLAMIC BANKING: ISLAMIC SOCIAL REPORTING PRACTICES OF BANK ALADIN SYARIAH - Ahmad, Syafar; Setiawan, Ricky; Muflikhah, Itsna; Jauhari, Yustika; Uksi, Rafika; Virginia, Winda Ayu (Jurnal Aplikasi Perpajakan, 2025)
This study aimed to analyze the level of Islamic Social Reporting (ISR) implementation at PT Bank Aladin Syariah Tbk using an ISR index specifically developed for evaluating Sharia-based social disclosure. The analysis was conducted on Bank Aladin’s 2024 Annual Report by assessing six main ISR themes, namely finance and investment, products and services, employees, community, environment, and corporate and Sharia governance. The results showed that Bank Aladin Syariah disclosed approximately 77% of the total 43 ISR items. The themes with the highest level of disclosure were finance & investment and Sharia governance, while the environmental theme had the lowest disclosure.These findings indicated that Bank Aladin Syariah had made efforts to implement Islamic social accountability principles, although improvements were still needed in reporting environmental aspects and community social activities.This study provided empirical contributions in measuring the consistency of Sharia-based social reporting in digital banking institutions in Indonesia and strengthened the application of Shariah Enterprise Theory values in modern accounting practices